Toxic Elite Consensus and Leadership Gaps as the Main Driver of Nigeria’s Crisis of Nationhood - Ososona, Tosin (Journal of Central and Eastern European African Studies, 2024)
The 61 years of Nigeria’s post-colonial political history has been one of different unending experiments to create a sustainable political and economic order that serves the Nigerian people. During this period, Nigeria has witnessed violent and unconstitutional political changes, long periods of military dictatorships, persistent cycles of electoral violence, inter and intra ethnic conflicts, and persistent economic and social policy reversals that have worsened Nigeria’s performance on almost all socio-economic indicators and the latest security challenges that have created doubt about the viability of the Nigerian state. Against this backdrop, this paper undertakes a historical analysis of the composition and capacity of the different elite clusters in Nigeria and how these clusters have impacted governance and the sustainability of Nigerian statehood. The paper also investigates the link between Nigeria’s current security crisis and the failure of governance that is underpinned by a toxic and extractive elite consensus and failure of leadership across the board. The paper adopts qualitative historical analysis and recommends the creation of a positive and developmental elite governance pact as one of the sustainable ways of addressing the looming implosion of the Nigerian state.